Altered neural oscillation patterns and functional connectivity in postherpetic neuralgia: evidence from resting-state EEG - Gao, Fei; Wang, Mengru; Jia, Huibin; Georgiev, Georgi V.; Feng, Yi; Li, Wenxia (Frontiers in Pain Research, 2025)
Postherpetic neuralgia (PHN) is a debilitating chronic pain condition that significantly affects the quality of life, often leading to physical discomfort, emotional distress, and psychological comorbidities, such as depression and anxiety. This study aimed to systematically assess the neural oscillatory activity and functional connectivity patterns in patients with PHN using resting-state electroencephalography (EEG). Overall, 21 patients with PHN and 17 healthy controls participated in this study. Resting-state EEG data were collected and analyzed. Power spectrum density analysis was conducted to compare frequency band activity, and correlation analyses were used to examine associations between EEG power and psychological symptoms. Functional connectivity was assessed using the weighted phase lag index. Power spectrum density analysis revealed significantly higher EEG power across the delta, theta, alpha, beta, and gamma frequency bands in patients with PHN compared with controls. Correlation analyses indicated that delta and theta frequency band power were positively associated with the Beck Depression Inventory scores, whereas delta frequency band power was negatively correlated with the State Anxiety Inventory scores. Additionally, functional connectivity analysis demonstrated reduced gamma-band connectivity in patients with PHN, particularly in regions of the sensorimotor and pain modulation networks. These findings suggest that PHN is characterized by widespread hyperactivity in neural circuits, accompanied by disrupted interregional communication. These results provide valuable insights into the neurophysiological mechanisms underlying PHN and highlight potential biomarkers for developing targeted neuromodulatory treatments to alleviate pain and improve the psychological well-being of affected individuals.